2017
DOI: 10.1007/s10826-017-0677-9
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Reports of Children’s Internalizing Symptoms: Associations with Parents’ Mental Health Symptoms and Substance Use Disorder

Abstract: This brief report examined the unique associations between parents’ ratings of child internalizing symptoms and their own depression and anxiety in families with parental substance use disorder (SUD). Further, we examined whether parental SUD (father only, mother only, both parents) was related to discrepancy in mothers’ and fathers’ reports of children’s internalizing symptoms. Participants were 97 triads (fathers, mothers) in which one or both parents met criteria for SUD. Polynomial regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
2
12
0
1
Order By: Relevance
“…There is a well-established literature that describes the difficulty parents have in rating HRQOL outcomes of their children, particularly internalizing symptoms (eg, anxiety, depressive symptoms, anger, stress). [66][67][68][69][70] In 2 studies, patients were more likely to report better HRQOL outcomes compared with their parents, 44,53 whereas in another study, both reported comparable or similar HRQOL scores. 57 Differences in HRQOL outcomes reported by patients and parents could be related to the psychosocial distress parents experience post-HSCT while providing care for their other children as well, and that the improvement in each domain may not be immediately apparent to the parents.…”
Section: Discussionmentioning
confidence: 99%
“…There is a well-established literature that describes the difficulty parents have in rating HRQOL outcomes of their children, particularly internalizing symptoms (eg, anxiety, depressive symptoms, anger, stress). [66][67][68][69][70] In 2 studies, patients were more likely to report better HRQOL outcomes compared with their parents, 44,53 whereas in another study, both reported comparable or similar HRQOL scores. 57 Differences in HRQOL outcomes reported by patients and parents could be related to the psychosocial distress parents experience post-HSCT while providing care for their other children as well, and that the improvement in each domain may not be immediately apparent to the parents.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of parents, they may not report their children's problems to avoid being stigmatized or to conceal a possible intra-family conflict (Grills & Ollendick, 2002). It can also be influenced by the parent's own psychopathology (Kelley et al, 2017) that they themselves have suffered or are currently suffering from ED. In the case of adolescents, factors such as age, type of problem, and demands of the assessment setting are significant aspects to be considered by the clinician (Smith, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Dies mag daran liegen, dass internalisierende Störungen generell von Eltern weniger gut wahrgenommen werden als externalisierende Störungen, insbesondere wenn Eltern selbst belastet sind (Los Reyes und Kazdin 2005 ; Kelley et al. 2017 ). Der Befund verdeutlicht umso mehr, dass spezielle Gruppen, die bereits vor der Pandemie besonderen Risiken ausgesetzt waren, dies auch während der Pandemie sind.…”
Section: Diskussionunclassified